Inclusion under the Mental Capacity Act (2005): A review of research policy guidance and governance structures in England and Wales - Hayley Ryan; Rob Heywood; Oluseyi Jimoh; Anne Killett; Peter E Langdon; Ciara Shiggins; Karen Bunning (Wiley, 2021)
Abstract Objective To investigate how people with communication and understanding difficulties, associated with conditions such as dementia, autism and intellectual disability, are represented in research guidance supplementary to the Mental Capacity Act (MCA: 2005) in England and Wales. Methods A documentary survey was conducted. The sample comprised the MCA Code of Practice (CoP: 2007) and 14 multi‐authored advisory documents that were publicly available on the Health Research Authority website. Textual review of key words was conducted followed by summative content analysis. Results Representation of people with communication and understanding difficulties was confined to procedural information and position statements that focused mainly on risk management and protection. Whilst a need to engage potential participants was recognized, guidance provided was imprecise. Conclusions Tensions exist between the protection versus empowerment of people with communication and understanding difficulties in research. The development of structured, evidence‐based guidance is indicated. Patient or public contribution People with communication and understanding difficulties and carers participated in a working group to explore, discuss and interpret the findings.